2011
DOI: 10.1590/s0100-40422011000200026
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e quantificação de contaminantes em aguardentes de cana

Abstract: Recebido em 26/1/10; aceito em 27/8/10; publicado na web em 24/11/10 ANALYSIS OF ORGANIC CONTAMINANTS AND COPPER IN CACHAÇA. The objective of the present study was the evaluation of the presence of organic and inorganic contaminants in samples of aged cachaça from the South of the state of Minas Gerais. Furfural, methanol and copper were determined by colorimetric reactions, while the analyses of ethyl carbamate and acrolein were performed by GC/ MS and HPLC, respectively. High levels of furfural and copper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 20 publications
8
41
1
10
Order By: Relevance
“…The difference in the amount of these compounds may be directly related to the storage time. These results are in agreement with those found by Madrera et al (2003) [10] who observed differences in the contents and in the presence of gallic acid and syringaldehyde during aging in addition to the presence of derivatives of cinnamic aldehyde present in the distillated beverage as brandy with different storage times.…”
Section: Quantification Of Phenolic Compoundssupporting
confidence: 93%
“…The difference in the amount of these compounds may be directly related to the storage time. These results are in agreement with those found by Madrera et al (2003) [10] who observed differences in the contents and in the presence of gallic acid and syringaldehyde during aging in addition to the presence of derivatives of cinnamic aldehyde present in the distillated beverage as brandy with different storage times.…”
Section: Quantification Of Phenolic Compoundssupporting
confidence: 93%
“…Routes for the formation of EC in distilled spirits during the distillation of the beverage and during storage have been proposed, considering cyanide, ethanol, copper and photochemically activated compounds as precursors. Although some authors believe that the distillation of cachaça in copper alambics promotes the metal-catalysed formation of EC (5,13,38), it has been shown in recent studies that there is no correlation between the concentration of copper and that of EC in cachaça (16,17,27,28,39).…”
Section: Resultsmentioning
confidence: 99%
“…The copper content of the beverages analyzed in southern Minas Gerais was higher than that recommended in 16.67% of the samples, and the content in one evaluated sample was as high as 9 mg L -1 (Zacaroni et al, 2011). Marinho et al (2009) observed that the copper content in the cachaça produced in Goiás was as high as 8.80 mg L -1 .…”
Section: Introductionmentioning
confidence: 90%